Pelatihan Software R Bagi Dosen Universitas Al-Syariah Mandar - Annas, Suwardi; Nusrang, Muhammad; Irwan, Irwan; Rais, Zulkifli; Ruliana, Ruliana (Panrannuangku Jurnal Pengabdian Masyarakat, 2023)
This Community Partnership Program (PKM) partner is a lecturer at FKIP Al-Syariah Mandar University. The problems are: (1) R as an open source software that is free of the license is not widely known in scope, (2) Lack of skills in statistical data analysis mainly related to regression analysis, path analysis, and SEM using R. The methods used are lectures, demonstrations, discussions, questions and answers, and co-partners. The results achieved are (1) partners have R software knowledge related to downloading and installing the software, (2) partners have superior knowledge possessed by the R package, (3) partners have knowledge and ability to analyze data related to path analysis and SEM analysis with using R.